Calcification of hydrophilic acrylic intraocular lenses following secondary surgical procedures in the anterior and posterior segments. Issue 12 (23rd February 2019) - Darcy, Kieren; Apel, Andrew; Donaldson, Mark; McDonald, Robert; Males, John; Coote, Michael; Werner, Liliana; Chan, Elsie
Abstract : Aims: To report 15 cases of intraocular lens (IOL) calcification following intraocular surgery and to identify common risk factors. Methods: A retrospective case review of patients with IOL calcification reported from the Royal Victorian Eye and Ear Hospital, Melbourne, Australia, and six surgeons in private practice in the Australian states of Victoria, New South Wales and Queensland. Results: 15 cases of IOL calcification were identified. Eight cases were in hydrophilic acrylic IOLs and seven in hydrophilic acrylic IOLs with hydrophobic surface properties. Five cases occurred following intraocular injection of gas during endothelial keratoplasties. Two cases occurred following pars plana vitrectomy where gas was used. The remaining eight cases did not involve the injection of any intraocular gas; six cases were following trabeculectomy surgery, and two cases were after insertion of a 'piggyback' sulcus IOL. In each case, the calcification had a characteristic pattern, being centrally placed in the pupillary zone, mainly affecting the anterior lens surface. Conclusion: The aetiology of IOL calcification is not fully understood, although there are known risk factors such as using hydrophilic acrylic materials and the use of intraocular gas. Surgical consideration of a patient's ocular comorbidities before IOL implantation is an important tool to mitigate some of this risk.